Cardiology referrals before and during the COVID-19 pandemic: a health service evaluation. (2nd July 2021) - Kwok, Chun Shing; Bennett, Jessica; Curry, Sonia; Jackson, Debbie; Burke, Hayley; Beeston, Michelle; Powell, Elizabeth; Gunter, Bob; Cripps, James; Jones, Angela; Bethell, Helen; Fogarty, Lisa; et al.
Abstract : Background/Aims: The COVID-19 pandemic has resulted in unprecedented changes to healthcare services. This study aimed to evaluate the impact of the COVID-19 pandemic on referrals to cardiology services in a tertiary hospital. Methods: Royal Stoke University Hospital has a cardiac assessment nurse team that provides rapid access to specialist cardiology opinion. All referrals are recorded on a database, which was used to determine how COVID-19 affected the number and types of referrals to cardiology during March–September 2019 and March–September 2020. Results: A total of 12 447 referrals were made to the cardiac assessment nurse teams over the evaluation period. Compared to the average number of referrals across all months, there was a decline of 10.5%, 31.2% and 18.5% during March, April and May 2019 respectively. Comparing 2020 to 2019, there were more 999 calls (17.7% vs 15.7%) and accident and emergency referrals (46.5% vs 45.0%), and fewer interhospital referrals (16.0% vs 19.6%). In terms of advice provided for the 999 referrals, a greater number were advised to go to the accident and emergency department (10.5% vs 0%) and direct phone advice provided to those in other settings increased (11.7% vs 0.1%) in 2020. Conclusions: The COVID-19 pandemic was associated with a reduction in the number of overall referrals to cardiology, while also demonstrating a shift towards more advice to attend the accident and emergency department for assessment or direct phone advice being provided about management in the community.